PENINGKATAN KOMPETENSI PROFESIONAL GURU DALAM MENYUSUN LAPORAN PENELITIAN TINDAKAN KELAS MELALUI MODEL PEMBINAAN CLCK (CONTOH,LATIHAN,CONTROL,KERJA MANDIRI) BERBASIS MENTORING DI MAN 6 PASAMAN BARAT - PASTAL PASTAL (STKIP Pesisir Selatan, 2019)
Based on observations of the competence of teachers MAN 6 Pasaman Barat in compiling a class action research report found the phenomenon that the professional competence of teachers in preparing classroom action research is still low. The purpose of this study is to describe and obtain information about improving teacher professional competence in preparing classroom action research reports through the CLCK coaching model (Example, Exercise, Control, Independent Work) based on MAN 6 Pasaman Barat. This research is a madrasa action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 13 MAN 6 Pasaman Barat teachers. Research data were collected using observation sheets. Data were analyzed using percentages. Based on the results of research and discussion, it can be concluded that the mentoring model based on CLCK can improve the ability of teachers to prepare class action research reports at MAN 6 Pasaman Barat. Analysis of the quality of PTK reports made by teachers shows that the teacher's professional competence in preparing class action research reports increases from cycle I to cycle II. The teacher's professional competence in preparing the class action research report in cycle I was 77.69 (enough) increased to 84.69 (good) in cycle II with an increase of 7.00 points.